THE ROLE OF MOBILE APPLICATIONS IN ENHANCING ENGAGEMENT AMONG STUDENTS WITH DYSLEXIA WITHIN ENGLISH LANGUAGE INSTRUCTION - Gazieva Saida Turgunovna (Modern American Journals, 2025)
This paper examines strategies to address dyslexia in primary English education within Uzbekistan’s modernization agenda. Drawing on inclusive pedagogy, multisensory methods, ICT, and speech-therapy support, we outline early screening criteria and classroom routines that build letter recognition, accurate writing, and pronunciation. We contextualize bilingual challenges (Uzbek–English), typical phoneme-grapheme confusions, and teacher principles for integration, continuity, interactivity, and resource efficiency. Evidence from trials in general schools and alignment with national 2030 objectives indicate improved speech competence and learner motivation. We propose a practical model combining family–kindergarten–school collaboration, data-informed monitoring, and authentic tasks to reduce barriers and scale effective interventions, nationwide adoption.
Keywords: Dyslexia, primary-education, bilingualism, ICT, multisensory, inclusive-pedagogy, speech-therapy, early-screening, pronunciation